56. PITUICYTOMA: A CASE REPORT AND LITERATURE REVIEW. (February 2015) - Subramanian, Vishnu; Shingde, Meena
Abstract : Background: The pituicytoma, or infundibuloma, is an exceptionally rare sellar-suprasellar glial neoplasm of adults with low proliferative activity (WHO grade I).1, 2 They are thought to arise from the pituicytes, which are specialised glial cells of the neurohypophysis.3 Less than 60 cases are reported so far. Case report: A 37-year-old female presented with amenorrhoea. No other clinical or neuro-endocrine symptoms were present. MRI brain showed a 22 mm intrasellar/suprasellar mass. Frozen section showed a spindle cell tumour. Histology showed cellular tumour with spindle cells arranged in short fascicles and sheets with focal storiform and packeted pattern. The tumour cells had an oval to elongated nuclei with pinpoint nucleoli. Scattered dilated stag-horn-like blood vessels and patchy lymphocytic infiltrates were present. No whorls, psammoma bodies, cytoplasmic granularity, eosinophilic granular bodies or Rosenthal fibres were noted. No mitotic figures or necrosis were noted. The spindle cells were strongly immunoreactive to S-100 protein, BCL-2, and CD99; patchy strong reactivity to GFAP and EMA; patchy weak reactivity to synaptophysin, and CD31; negative to broad-spectrum cytokeratins (AE1/AE3), chromogranin and CD34. The Ki-67 (MIB1) proliferation index was 2% to 8%. Conclusion: We present a case report of this rare entity, review available literature, and discuss the clues to differentiate it from other spindle cell tumours such as granular cell tumour, meningioma, pilocytic astrocytoma, schwannoma and other lesions, which are common to the sellar-suprasellar site, as accurate diagnosis is essential to guide the appropriate management.